Using online teaching threshold concepts in transformative professional learning curricula for novice online educators : final report. - Northcote, Maria; Gosselin, Kevin; Reynaud, Daniel; Kilgour, Peter; Boddey, Chris; McLoughlin, Catherine; Rickards, Tony; Boddey, Kerrie (Dept of Education and Training Australia, 2017)
Along with the continued growth in online education across the tertiary sector, there is a strong need for university educators to design and teach within online courses in a way that enhances high quality student learning. Educators who are new to teaching online represent a group who require urgent professional development support and resources within tertiary education concepts. This is the final report from a project that set out to develop research-informed curriculum design guidelines that may be used by academic developers and university administrators to develop professional learning programs for novice higher education online teachers. It achieves this by exploring the threshold concepts held by experienced and novice online educators, and the perceptions of online learning by teachers and students.